Review of Surface-Defect Detection Methods for Industrial Products Based on Machine Vision - Quan Wang; Mengnan Wang; Jiadong Sun; Deji Chen; Pei Shi (IEEE Access)
Industrial defect detection is crucial for ensuring product quality and production efficiency, playing a pivotal role in advancing smart manufacturing. This paper reviews defect detection technologies for various industrial products, including metals, textiles, and printed circuit boards, and introduces an innovative classification system. It also offers a detailed analysis of recent developments and practical applications of large models in industry defect detection. First, the basic principles of industrial defect detection are outlined. The detection methods are then categorized into three main groups: traditional image processing, machine learning, and deep learning, with their principles, case studies, limitations, and future development directions analyzed. Traditional methods consist of image preprocessing, segmentation, and feature extraction. Machine learning methods are divided into point-distance-based, hyperplane-based, tree-based, and neural network-based classification algorithms. Deep learning models are classified into two types: accuracy-oriented and efficiency-oriented. The paper organizes industrial defect datasets by type (multi-product and single-product), evaluates data quality and availability, and summarizes common evaluation metrics for accuracy, efficiency by task requirements. It also compares the latest methods on two public datasets to guide further research in defect detection. Real-world examples illustrate the end-to-end process, from data processing and hardware configuration to model training and deployment, while exploring the value and limitations of these technologies from the perspective of industry stakeholders. Finally, a systematic analysis of the key challenges and corresponding solutions is presented at the data and performance levels, and looks forward to the future direction of technological development, highlighting innovative paths and application potentials.